Pengaruh Pembinaan, Sertifikasi, dan Sosialisasi Terhadap Kelancaran Bisnis UMKM di Kabupaten Mojokerto Menggunakan Analisis Regresi Linear Berganda - Billy Gandis Pradana; Hafid Syaifullah (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
The economy of a country is influenced by many important factors, including its industry and trade. This research was conducted to determine the influence of coaching, certification and socialisation activities on the smooth running of MSME businesses in Mojokerto Regency. Data collection was carried out by distributing questionnaires to the MSMEs concerned and then processed with SPSS software using multiple linear regression. The results of the study began with a data quality test that produced all variables that were valid and reliable, then the classical assumption test produced normally distributed data that passed the multicollinearity and heterokedasticity tests. For the equation of the three independent variables in the state of zero, the variable of business smoothness is valued at 11.846, if the variable of coaching activities increases by one unit, there will be a decrease in the variable of business smoothness by 0.045, if the certification and socialisation activities increase by one unit, there will be an increase in the variable of business smoothness by 0.021 and 0.086. The hypothesis test produced a coefficient of determination of 0.012, so the three independent variables explain the business smoothness variable by 1.2%, the F test concluded that the three independent variables (simultaneous) did not have a significant effect on the business smoothness variable, the T test concluded that the three independent variables (partial) did not have a significant effect on the business smoothness variable.